Autonomy, competence, and relatedness in mathematics education: a self-determination perspective on future professional teachers - Siregar, Nurfadilah; Hartoyo, Agung; Nurhasanah Siregar (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study explore the self-determination profiles of postgraduate mathematics education students, emphasizing how autonomy, competence, and relatedness contribute to their readiness and motivation to pursue teaching as a professional career. Method: A quantitative-descriptive approach was employed, using a validated self-determination questionnaire distributed to 47 postgraduate students and alumni from 2020 to 2024. The instrument measured three SDT dimensions (autonomy, competence, and relatedness) through 24 positive and negative statements. Descriptive and comparative analyses were applied to identify dominant motivational patterns. Finding: Findings revealed high mean scores for autonomy and competence, indicating students’ confidence in decision-making and mastery of pedagogical knowledge. Relatedness also scored strongly, reflecting solid interpersonal engagement with peers and lecturers. Collectively, these outcomes depict a balanced SDT profile among future mathematics teachers. Significance: The study demonstrates that strong self-determination enhances students’ readiness to enter the teaching profession with intrinsic motivation, pedagogical confidence, and collaborative awareness. Strengthening these three SDT dimensions within teacher education curricula can cultivate mathematics educators who are reflective, adaptive, and committed to continuous professional development. This research underscores that fostering autonomy, competence, and relatedness is not only central to improving mathematics learning but also to shaping sustainable teacher professionalism in the modern educational landscape.